Discovery of Novel Sultone Fused Berberine Derivatives as Promising Tdp1 Inhibitors - Elizaveta D. Gladkova (Molecules, 2021)
A new type of berberine derivatives was obtained by the reaction of berberrubine with aliphatic sulfonyl chlorides. The new polycyclic compounds have a sultone ring condensed to C and D rings of a protoberberine core. The reaction conditions were developed to facilitate the formation of sultones with high yields without by-product formation. Thus, it was shown that the order of addition of reagents affects the composition of the reaction products: when sulfochlorides are added to berberrubine, their corresponding 9-O-sulfonates are predominantly formed; when berberrubine is added to pre-generated sulfenes, sultones are the only products. The reaction was shown to proceed stereo-selectively and the cycle configuration was confirmed by 2D NMR spectroscopy. The inhibitory activity of the synthesized sultones and their 12-brominated analogs against the DNA-repair enzyme tyrosyl-DNA phosphodiesterase 1 (Tdp1), an important target for a potential antitumor therapy, was studied. All derivatives were active in the micromolar and submicromolar range, in contrast to the acyclic analogs and 9-O-sulfonates, which were inactive. The significance of the sultone cycle and bromine substituent in binding with the enzyme was confirmed using molecular modeling. The active inhibitors are mostly non-toxic to the HeLa cancer cell line, and several ligands show synergy with topotecan, a topoisomerase 1 poison in clinical use. Thus, novel berberine derivatives can be considered as candidates for adjuvant therapy against cancer.